Integrating high-throughput phenotyping and genome-wide association analyses to unravel Mediterranean maize resilience to combined drought and high temperatures - Rongli Shi; Ana López-Malvar; Dominic Knoch; Henning Tschiersch; Marc C. Heuermann; Salar Shaaf; Delphine Madur; Rogelio Santiago; Carlotta Balconi; Elisabetta Frascaroli; Sekip Erdal; Carine Palaffre; et al. (Plant Stress)
Integrating phenomics and genomics is a promising approach to identify genetic factors that confer stress resistance to plants in certain phases. Differently adapted germplasm enables valuable insights into multiple plant stress resilience mechanisms. The dynamic responses of 106 Mediterranean maize inbred lines to combined drought and high temperature (D-HT) were investigated by high-throughput shoot phenotyping. Two experiments were conducted under control (25/20 °C, 70 % field capacity) and D-HT conditions (35/25 °C, 30 % field capacity). Stress was applied from 18 to 32 days after sowing, followed by recovery under control conditions. The stress treatment resulted in decreased plant height, projected shoot area, estimated shoot volume (ESV), as well as diminished relative growth rates during the vegetative phase. Additionally, photosynthetic parameters decreased significantly under D-HT, but normalized during a recovery phase. Stress indices, namely stress resistance, stress recovery and stress adaptability, were calculated based on ESV. Both, stress resistance and recovery contributed to maize resilience to D-HT, however they appear to be mediated through different processes. Genome-wide association studies (GWAS) were performed to dissect the genetic basis of maize resilience to D-HT-stress. Overall, associations with 201 unique single nucleotide polymorphism (SNP) markers and 89 linked candidate genes were detected. We conducted a detailed temporal analysis of trait development across stress and recovery phases, and evaluated the dynamics of the underlying genetic system. These findings contribute to refining our understanding of multiple plant stress resilience mechanisms in the face of ongoing global climate change and to advance future maize breeding to enhance stress resilience.